Jaspamide: Structure identification of cytotoxic and fungicide compound isolated from Stylissa flabelliformis sponges - Setyowati, Erna Prawita; ., Sudarsono; Wahyuono, Subagus (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
A research on the structure identification of cytotoxic and fungicide compound of Stylissa flabelliformis sponge has been conducted. The structure identification was analysed with spectroscopy ultraviolet, MS, 1HNMR and 13C-NMR methods.Based on the spectroscopic data and comparison with literatures, the compound was identified as jaspamide.Key words: sponge, Stylissa flabelliformis , jaspamide, structure elucidation